Assessment of Groundwater Recharge Using GIS (Journal on Geoinformatics, Nepal, 2010)
Pressure on drinking water is increasing tremendously due to the increase in population in Kathmandu valley. Groundwater is serving as one of main source of water supply in the valley. Due to the scarcity of surface water and high demand for drinking water, excess extraction of groundwater than it replenishes may cause negative effect to Kathmandu valley like subduction. Thus, proper quantification of groundwater recharge must be done to de! ne sustainable extraction of the groundwater. This study is conducted with the aim to demonstrate the simple water balance model within the GIS environment in order to quantify the spatial distribution of groundwater recharge. The simple water balance model Thornthwaite and Marther (1955) was used to quantify the water balance components in the upper bagmati watershed. The study shows that the groundwater recharge is high at the northern part specifically where there is high water holding capacity.